2018
DOI: 10.1002/aah.10034
|View full text |Cite
|
Sign up to set email alerts
|

Retail Baitfish in Michigan Harbor Serious Fish Viral Pathogens

Abstract: Indigenous small cyprinid fish species play an important role in Great Lakes ecosystems and also comprise the backbone of a multimillion-dollar baitfish industry. Due to their widespread use in sport fisheries of the Laurentian Great Lakes, there are increasing concerns that baitfish may introduce or disseminate fish pathogens. In this study, we evaluated whether baitfish purchased from 78 randomly selected retail bait dealers in Michigan harbored fish viruses. Between September 2015 and June 2016, 5,400 baitf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Anglers and aquarists potentially play a role in these processes, as the transport and exchange of live individuals between and among these hobbyist groups establishes novel pathways and increases the frequency of translocation of propagules (Figure 6). Another pressing conservation issue related to non‐native fish in the context of anglers and aquarists is the translocation of diseases and parasites: recent research has shown that the activities of anglers can transmit diseases by introducing disease‐carrying baitfish (Boonthai et al, 2017, 2018). Thus, anglers and aquarists acting in concert may potentially pose a greater threat to the conservation of native freshwater ecosystems than the individual actions of these hobbyist groups alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anglers and aquarists potentially play a role in these processes, as the transport and exchange of live individuals between and among these hobbyist groups establishes novel pathways and increases the frequency of translocation of propagules (Figure 6). Another pressing conservation issue related to non‐native fish in the context of anglers and aquarists is the translocation of diseases and parasites: recent research has shown that the activities of anglers can transmit diseases by introducing disease‐carrying baitfish (Boonthai et al, 2017, 2018). Thus, anglers and aquarists acting in concert may potentially pose a greater threat to the conservation of native freshwater ecosystems than the individual actions of these hobbyist groups alone.…”
Section: Resultsmentioning
confidence: 99%
“…Intentional or unintentional release of baitfish is the most well‐studied angler‐related pathway of aquatic invasions (Drake & Mandrak, 2014). Survey data on fishing bait usage suggest that baitfish and crayfish are frequently stored before or after fishing, and are translocated between fishing spots (Banha & Anastácio, 2015; Boonthai et al, 2018; Ward, Cudmore, Drake, & Mandrak, 2011). Storing baitfish for longer than a single fishing trip involves some type of vessel, such as an aquarium.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high rates of live baitfish use and the number of anglers using them, this pathway is both high volume and complex, with millions of individual fish moving long distances overland every year (Drake and Mandrak 2014). The concern is warranted with increasing reports of nontarget (including nonnative) species and potentially problematic pathogens in live baitfish available for retail sale at some bait shops in the Great Lakes region (e.g., Boonthai et al 2017, 2018; Mahon et al 2018; Snyder et al 2020; McEachran et al 2021b). While the legal use of live baitfish carries negligible risk of pathogen spread via incidental contact with hooked baitfish, the deliberate release of live, unused baitfish by anglers presents a more serious risk for aquatic invasive species and pathogen dispersal (Rodgers et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The movement of live bait for use in recreational angling has been identified as a particularly high‐risk and poorly understood pathway for the spread of several concerning aquatic invasive species and pathogens (e.g., viral haemorrhagic septicaemia virus; Boonthai et al., 2017 , 2018 ; Mahon et al., 2018 ; McEachran et al, accepted ; Nathan et al, 2015 ) in the Great Lakes region of the United States (Drake & Mandrak, 2014 ; Goodchild, 2000 ; Litvak & Mandrak, 1993 ; Ludwig & Leitch, 1996 ). Baitfish are small fish, most commonly minnows of the family Leuciscidae (formerly Cyprinidae; Schönhuth et al., 2018 ; Tan & Armbruster, 2018 ), that are fed as forage in aquaculture settings and are used as bait by recreational anglers.…”
Section: Introductionmentioning
confidence: 99%